Osman Attilâ’nın Şiirlerinde Tema-I ‘Ben’e Yönelik Temalar - Şengül, Abdullah (Afyon Kocatepe Üniversitesi, 2004)
Cumhuriyet devri şair ve yazarları arasında yer alan Osman Attilâ, elli altı yıllık ömrünün büyük bir kısmında şiirle uğraşmıştır. Halkevleri ve Ülkü Mecmuası onun için okul olmuştur. Şiirlerinde “ben”e yönelik temalar ilk kitabından itibaren ağırlıkla işlenir. Zamanla “toplumsal” temalara doğru bir yönelişin olduğu görülür.

Osman Attilâ who is among poets and authors of Republic period, has concerned with poems a great part of a fifty-six-year-old life. Halkevleri and Ülkü Mecmuası have been an “ecole” for him. From his first book on, themes which are directed towards “ego” are treated largely in his poems. But as time passed, a tendency towards social themes is seen in his works.
Theme in the poets of Osman Attilâ-I Themes Which Are Directed Towards ‘Ego’)
Keywords: Osman Attilâ; Şiir; Tema